Implementation of Traditional Knowledge Protection of Enbal Processing - Narwadan, Theresia Nolda Agnes; Labetubun, Muchtar Anshary Hamid; Fataruba, Sabri (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Implementation and regulations governing the protection of traditional knowledge is still considered less effective. The law is expected to be able to overcome various problems that arise related to the protection of traditional knowledge from the community, especially the Kei Islands community on enbal processing knowledge.Purposes of the Research: The purpose of this study was to determine and analyze the implementation of the protection provided by the copyright law on the ownership of a traditional knowledge which in this case is the processing of enbal traditionally done as a staple food in the Kei Islands community.Methods of the Research: The research method used is juridical empirical.Results of the Research: The results obtained are the implementation of the protection provided by the copyright law on the ownership of a traditional knowledge which in this case is the processing of enbal traditionally done as a staple food in the Kei Islands community has actually been regulated in Article 38 of the Copyright Act. However, this protection can be provided if the community continues to maintain traditional processing without the help of modern tools when processing enbal into staple foods.